2022
DOI: 10.1186/s13195-022-01029-0
|View full text |Cite
|
Sign up to set email alerts
|

Fully automated and highly specific plasma β-amyloid immunoassays predict β-amyloid status defined by amyloid positron emission tomography with high accuracy

Abstract: Background Clinicians, researchers, and patients alike would greatly benefit from more accessible and inexpensive biomarkers for neural β-amyloid (Aβ). We aimed to assess the performance of fully automated plasma Aβ immunoassays, which correlate significantly with immunoprecipitation mass spectrometry assays, in predicting brain Aβ status as determined by visual read assessment of amyloid positron emission tomography (PET). Methods The plasma Aβ42/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 51 publications
0
21
2
Order By: Relevance
“…A similar technique applied by some studies is known as immunoprecipitation-free liquid chromatography-mass spectrometry (IP-free LC-MS), which measures Aβ species with mass spectrometry, but without antibody purification prior to measurement by LC-MS [22,34]. Studies that use a bead-based immunoassay, for example, the SIMOA assay or some high-sensitivity chemiluminescence assays, use beads for specific Aβ species antibody binding and indirect quantification, sometimes after amplification [20,22,28,[35][36][37][38][39][40]. In contrast, other studies apply plate-based immunoassays (such as an ELISA assay), in which a binding antibody is adsorbed onto a plate where it binds the Aβ species, and a second antibody binds to another Aβ antigen, forming what is known as a "sandwich" between the two antibodies [22,25,28,36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar technique applied by some studies is known as immunoprecipitation-free liquid chromatography-mass spectrometry (IP-free LC-MS), which measures Aβ species with mass spectrometry, but without antibody purification prior to measurement by LC-MS [22,34]. Studies that use a bead-based immunoassay, for example, the SIMOA assay or some high-sensitivity chemiluminescence assays, use beads for specific Aβ species antibody binding and indirect quantification, sometimes after amplification [20,22,28,[35][36][37][38][39][40]. In contrast, other studies apply plate-based immunoassays (such as an ELISA assay), in which a binding antibody is adsorbed onto a plate where it binds the Aβ species, and a second antibody binds to another Aβ antigen, forming what is known as a "sandwich" between the two antibodies [22,25,28,36].…”
Section: Resultsmentioning
confidence: 99%
“…In general, the immunoassays displayed lower AUCs across most studies that used a PET reference standard. Studies using a SIMOA assay had a weighted average AUC value of 0.690 across ten cohorts [20,22,24,28,[35][36][37], chemiluminescence assays had a weighted average AUC of 0.818 across six cohorts [22,28,38,40], IP-free LC-MS assays had a weighted average AUC of 0.742 across five cohorts [22,34], and ELISA assays had a weighted average AUC of 0.734 across three cohorts [22,25,36] (Table 1, Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…The core AD biomarkers for amyloidosis (Aβ42 and ratio Aβ42/Aβ40) have been measured in plasma for the diagnosis of AD, even in the early stages [ 13 , 14 , 15 ]. A previous study showed the consistency of the plasma ratio Aβ42/Aβ40 as a predictor of AD [ 16 ], and plasma p-Tau181 has been studied as biomarker for the disease [ 17 , 18 , 19 ]. Moreover, these recent studies pointed to plasma p-Tau181 and other hyperphosphorylated Tau (p-Tau231, p-Tau217) as the most sensitive plasma biomarkers for AD diagnosis [ 18 , 19 ], even in the early stages [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“… What are the characteristics of the nervous system that are different (see Challenge 2) at the onset [ 113 ] of pathological aging? What is the detailed temporal relationship between amyloid and tau pathology, and the various biomarkers and behavioral changes in the database [ 114 , 115 , 116 ]? …”
Section: Specific Challengesmentioning
confidence: 99%
“…What is the detailed temporal relationship between amyloid and tau pathology, and the various biomarkers and behavioral changes in the database [ 114 , 115 , 116 ]?…”
Section: Specific Challengesmentioning
confidence: 99%